Statut des Domkapitels Eichstätt vom 21. März 2005 (Abl Eichstätt 152 [2005] 104-118) - Schimmöller, Klaus; Diözese Eichstätt; Winter, Manfred; Mixa, Walter 1941- (2005)
Auch veröffentlicht in: KABl. Eichstätt 152 [2005] 104 - 118
Aufsatz
Keywords: Katholische Kirche -- Diözese Eichstätt; Katholische Kirche; Katholische Kirche; Katholische Kirche -- Diözese Würzburg -- Domkapitel; Domkapitel; Satzung; Partikularrecht; Deutschland; Eichstätt; Norm